Faith-based organizations and social welfare: associational life and religion in contemporary western europe - Manuel, Paul Christopher; Glatzer, Miguel (Palgrave studies in religion, politics, and policy, 2019)
Intro -- Praise Page -- Dedication -- Foreword -- Acknowledgments -- Contents -- About the Editors -- Contributors -- List of Figures -- List of Tables -- Chapter 1: "Use Words Only If Necessary": The Strategic Silence of Organized Religion in Contemporary Europe -- Structure of the Volume -- Comparative Perspectives -- First Comparative Dimension: The Contemporary West European Religious Marketplace -- Second Comparative Dimension: Level of Democratization Across Western Europe -- Third Comparative Dimension: Welfare State Type Across Western Europe -- Fourth Comparative Dimension: Vulnerability to the 2008 Global Economic Crisis -- Our Comparative Dimensions: Summary -- A Preliminary Assessment: Key Themes from the Case-Studies -- Part I: Countries with a Dominant Religious Society -- Chapter 2: The Entanglement and Disentanglement of Church and State in Irish Social Policy -- Social Change in Ireland -- Economic Fluidity -- Poverty and Homelessness -- The Entanglement of Church and State in Ireland -- Social Policy -- Education -- The Entanglement of Catholic Teaching with Public Morality -- Church and State Diminishment -- The Challenge of Social Inclusion in Neo-liberal Ireland -- The Religious Divestment of Schools and Hospitals -- Schools -- Hospitals -- Can the State Manage the Divestment of Religious Influence? -- Religious Freedom -- A New Conscience -- Chapter 3: Religiously Oriented Welfare Organizations in Italy Before and After the Great Recession: Toward a More Relevant Role in the Provision of Social Services? -- Introduction -- The Italian Context: The Emergence of New Social Risks in a (Still) Predominantly Catholic Society -- The Italian Welfare State in Comparative Perspective -- Church and State Relations in the Social Policy Field: A Historical Perspective.